Start-up ecosystems as a framework for the cooperation between start-up companies and knowledge-based institutions in Poland - Domańska, Agnieszka (Ekosystemy startapowe jako ramy współpracy pomiędzy nowo utworzonymi przedsiębiorstwami a instytucjami opartymi na wiedzy w Polsce, 2018)
The aim of the article is to outline the picture of the Polish start-up ecosystem (in fact consisted of few ecosystems but functioning under the same scheme), i.e. its main actors and relations among them with the special focus put on the ways and “channels” the cooperation between start-ups and knowledge-based institutions (later termed K-BI) are to be realized.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 536, s. 49-59
Keywords: start-up company; knowledge-based institutions; start-up ecosystem; institution framework; business models; firmy typu start-up; ecosystem startupowy; współpraca nauki i biznesu